A review on correlations between fish freshness and pH during cold storage - Abbas, Kassim Ali; Mohamed, A.; Bakar, Jamilah; Ebrahimian, M. (Science Publications, 2008)
Freshness of fish in most markets was found to be the significant quality parameter. The state of fish freshness was assessed by various methods but most of them were costly, time-consuming and not user friendly tools which made the development of simple, easy, undemanding and reliable system for the evaluation of fish freshness unresolved goal. The findings of many researchers revealed that there was remarkable correlation between the pH and the fish freshness which suggested that this physical characteristic could be used as suitable tool for the analysis and fish freshness evaluation rather than sensory evaluation method which inherent many uncertainties. Based on this demand, this paper was established with the objective of reviewing the literature which focused on the pH as one of the simple and reliable freshness indicator for cold stored fish samples.